Contagion in the interbank market and its determinants - Memmel, Christoph; Sachs, Angelika (Journal of Financial Stability, 2013)
Carrying out interbank contagion simulations for the German banking sector for the period from the first quarter of 2008 to the second quarter of 2011, we obtain the following results: (i) The system becomes less vulnerable to direct interbank contagion over time. (ii) The loss distribution for each point in time can be condensed into one indicator, the expected number of failures, without much loss of information. (iii) Important determinants of this indicator are the banks’ capital, their interbank lending in the system, the loss given default and how equal banks spread their claims among other banks.